Study of characteristics of vortex tube - V. I. Kuznetsov; V. V. Makarov; A. S. Gritsay (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Based on the previously compiled physical and mathematical model of the vortex tube workflow, the calculation of the thermogasodynamic characteristics of the vortex tube with known geometric dimensions and their comparison with experimental data was carried out. The calculations take into account the exchange of work and heat between the axial and peripheral gas layers. The exchange of work is carried out due to the transfer of kinematic energy from the axis to the periphery by viscosity forces when tangential stresses occur. The difference of thermodynamic temperatures when heat is supplied from the periphery to the axis is taken into account. These phenomena reduce the cooling effect of the flow coming out of the diaphragm.